Impact of Allergic Contact Dermatitis on the Quality of Life and Work Productivity - H. Kalboussi; I. Kacem; H. Aroui; O. El Maalel; M. Maoua; A. Brahem; S. El Guedri; S. Chatti; N. Ghariani; N. Mrizak (Dermatology Research and Practice)
Background. Allergic contact dermatitis (ACD) is a common chronic skin disease that generates considerable public-health and socioeconomic costs. This disease affects the quality of life and the occupational activity of patients. Aims. To assess the quality of life (QOL) of patients with ACD and study the impact of this disease on their work productivity. Methods. This is a cross-sectional study carried out from January 2012 to December 2014. All patients diagnosed with ACD in the Dermato-Allergology Unit of the Occupational Medicine Department at Farhat Hached University Hospital, in Sousse, were included. The impact of skin disease on the QOL of affected persons was assessed using the Dermatology Life Quality Index (DLQI). The work productivity was measured using the Work Productivity and Activity Impairment Allergic Specific questionnaire (WPAI: AS). Results. The study population consisted of 150 patients. The average score of DLQI was 6.5. Over the previous 7 days, absenteeism rate was 25.9 ± 15.3%, presenteeism rate was 50.2 ± 32%, overall work productivity loss was 29.6 ± 19.4%, and daily activity impairment was 50.4 ± 32.3%. The DLQI score was significantly associated with atopy (p = 0.03), relapses strictly greater than 10 (p = 0.02), presenteeism (p <10−3), overall work productivity loss (p = 0.01), and daily activity impairment (p = 0.03). Conclusion. The impact of ACD on QOL and occupational activity seems important and requires specific attention from the occupational physician.